AAU Professional skills Lab (ProLab): Promoting Transversal Skill Development in STEM through Student Self-Selected Interdisciplinary Workshops - Clausen, Nicolaj Riise; Bertel, Lykke; Nørgaard, Bente; Lyngdorf, Niels Erik Ruan; Velmurugan, Giajenthiran; Guerra , Aida Olivia Pereira de Carvalho (Proceedings from the International Research Symposium on Problem-Based Learning (IRSPBL), 2025)
The growing demand for well-rounded STEM professionals underscores the importance of developing non- technical professional skills like communication, collaboration, critical thinking, AI literacy, and systems thinking, or transversal skills, alongside technical expertise. Aalborg University (AAU) has long refined methods for fostering such transversal skills within its PBL framework. This paper presents AAU ProLab, a new initiative that replaced program-specific workshops with full-day interdisciplinary workshop events, bringing together students from various programs and semesters across the faculties of Engineering, Natural Science, and IT & Design. The initiative aimed to enhance motivation by allowing students to choose workshops aligned with their interests and connect across disciplines. The evaluation, based on an online student survey, included three quantitative questions on recommendation, relevance, and achievement of learning objectives, alongside qualitative feedback. Results showed high satisfaction, with students valuing interdisciplinarity, workshop diversity, and freedom of choice. Suggestions for improvement centered on clearer communication, streamlined registration, and strengthening active learning. Subsequent editions have already addressed these issues through a dedicated Moodle space for information, a simplified registration model, and revised workshop allocation. Most workshops now emphasize interactive, application-oriented learning, supported by feedback from both students and facilitators. ProLab thus represents a promising platform for supporting interdisciplinary learning and transversal skill development.